Small Business Empowerment Strategy in the Agricultural Sector Through Digital Entrepreneurship - Achmad, Adnan; Karto , Andriani; Asril, Akmil (International Journal of Management Science and Information Technology, 2024)
This study looks at how digital entrepreneurship is being used by small enterprises in the agriculture industry to empower them. It focusses on how this is affecting market access, production efficiency, and bolstering competitiveness. The advent of digital transformation has presented small enterprises with novel prospects to surmount customary constraints, including restricted availability of markets, finance, and technology. This research employs a qualitative methodology and a case study approach to investigate how small agricultural firms might use digital technologies, like e-commerce platforms and the Internet of Things (IoT), to increase market access and productivity. In-depth interviews with small business owners, technology suppliers, and other stakeholders were used to gather data. Direct observation and document analysis were also used. The results of this study show that small enterprises' operational efficiency and revenue are greatly increased when digital entrepreneurship is implemented. Collaboration with a range of stakeholders, including the government and academic institutions, and sufficient digital literacy have shown to be crucial for the effective execution of this plan. This study also emphasises how crucial it is to create both domestic and global business networks in an effort to increase market penetration and boost the competitiveness of small enterprises in the agriculture industry. In order to increase the sustainability and competitiveness of small enterprises in the agriculture sector, this study makes recommendations based on its results for policy makers and industry participants to assist the widespread adoption of digital entrepreneurship.